Physiological importance of the heterodisulfide of coenzyme M and 7-mercaptoheptanoylthreonine phosphate in the reduction of carbon dioxide to methane in Methanobacterium. - Bobik, T A (1988)
The heterodisulfide of the two coenzymes 2-mercaptoethanesulfonic acid (coenzyme M, HS-CoM) and N-(7-mercaptoheptanoyl)threonine O3-phosphate (HS-HTP) increased the rate of CO2 reduction to methane by cell extracts 42-fold. The stimulation resulted from activation of the initial step of methanogenesis, the production of formylmethanofuran from methanofuran and CO2. These results establish a role for this heterodisulfide (CoM-S-S-HTP) in the reduction of CO2 to formylmethanofuran. Evidence indicates that CoM-S-S-HTP is the labile intermediate that accounts for the coupling of the reduction of 2-(methylthio)ethanesulfonic acid by the methylreductase to formylmethanofuran biosynthesis, the "RPG effect." The heterodisulfide was found to be labile in cell extracts due to enzyme-catalyzed reduction and possibly thioldisulfide exchange.